Santripreneurship Development Through Hydroponic Vegetable Cultivation Technology At the Al-Ikhsan Islamic Boarding School, Banyumas Regency: Pengembangan Santripreneurship Melalui Teknologi Budidaya Sayur Hidroponik Di Pondok Pesantren Al-Ikhsan Kabupaten Banyumas - Nur Kholida Wulansari; Lafi N. Bayyinah; Mutala'liah; Ashlikhatul Fu’adah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Santri have an important role in future developments in various sectors. The younger generation after graduating will choose work rather than entrepreneurship. This is because when they were at school or at the Islamic boarding school they did not have the skills. Students' skills in entrepreneurship, called santripreneurship, need to be honed from an early age to realize students' independence after completing formal and informal schooling at Islamic boarding schools. Science and Technology-based PKM activities are carried out at the Al-Ikhsan Islamic Boarding School, Purwokerto. The aim of this activity is (1) to improve students' understanding (cognitive) and skills (psychomotor) in hydroponic vegetable production technology, and (2) to foster students' entrepreneurial spirit (santripreneurship) so that they can become entrepreneurs after graduating. Implementation methods include (1) counseling or material transfer, (2) hydroponic vegetable production practices, and (3) assistance in product marketing. The results of service activities show that there is an increase in knowledge and skills in hydroponic vegetable production starting from installation, planting, nutritional application to maintenance.